Keanekaragaman Jenis Vegetasi dan Profi l Habitat Burung di Hutan Mangrove Pulau Nyamuk Taman Nasional Karimunjawa - Nugroho Edi Kartijono; Margareta Rahayuningsih; Muhammad Abdullah (Biosaintifika: Journal of Biology & Biology Education, 2010)
Research on the vegetation diversity and bord habitat profi le has been carried outin the Mangrove Forest of Pulau Nyamuk in Karimunjawa National Park to examinethe relationship between vegetation types and mangrove habitat profi le and the spatialusage by birds. A transect method has been employed to survey the vegetation and thepoint count method was used to survey the birds. There were 14 vegetation types and 19species of birds from 14 families at two observational sites in mangrove forest in PulauNyamuk. Exchoecaria agallocha dominated the eastern part of Pulau Nyamuk, whereasLumnitzera racemosa dominated the northern part of the island. The vegetational spaceutilization by birds can be grouped based on the vertical vegetation stratifi cation, i.e. theland, the understorey, the subcanopy and the canopy.Keywords: mangrove vegetation, bird habitat, Pulau Nyamuk, Karimunjawa